2018
DOI: 10.1080/10872981.2018.1508267
|View full text |Cite
|
Sign up to set email alerts
|

Concerning trends in allopathic medical school faculty rank for Indigenous people: 2014–2016

Abstract: Background: Trends in faculty rank according to racial and ethnic composition have not been reviewed in over a decade.Objective: To study trends in faculty rank according to racial and ethnicity with a specific focus on Indigenous faculty, which has been understudied.Methods: Data from the Association of American Medical Colleges’ Faculty Administrative Management Online User System was used to study trends in race/ethnicity faculty composition and rank between 2014 and 2016, which included information on 481,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Nearly 30% of White medical school faculty members have the full professor rank, compared with less than 5% of American Indian and Alaska Native faculty. 25 It is necessary for institutions to move beyond outdated passive recruitment efforts, such as posting job descriptions and opportunities, to proactively reaching out to potential American Indian and Alaska Native candidates. The importance of a diverse faculty search committee cannot be overstated in efforts to broaden applicant pools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 30% of White medical school faculty members have the full professor rank, compared with less than 5% of American Indian and Alaska Native faculty. 25 It is necessary for institutions to move beyond outdated passive recruitment efforts, such as posting job descriptions and opportunities, to proactively reaching out to potential American Indian and Alaska Native candidates. The importance of a diverse faculty search committee cannot be overstated in efforts to broaden applicant pools.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 30% of White medical school faculty members have the full professor rank, compared with less than 5% of American Indian and Alaska Native faculty. 25 shown to increase the number of American Indian and Alaska Native college graduates who successfully matriculate into medical school. 27 These cultural and community elements help American Indian and Alaska Native students navigate cognitive dissonance as they learn to balance cultural identity inside and outside of the classroom.…”
Section: Jama Network Open | Medical Educationmentioning
confidence: 99%
“…An inadequate pool of AIANs and NHPIs matriculating into medical school directly leads to an inadequate pool of Indigenous medical school faculty. Our own prior work has shown that U.S. Indigenous faculty members, defined as AIAN and NHPI, represented the smallest percentage of U.S. allopathic medical school faculty at 0.11% and 0.18% respectively (Brodt et al, 2018), and that Indigenous faculty represented the lowest percentage of full professor faculty at 5.2% in 2016 for AIAN faculty and a decline from 4.6% to 1.6% between 2014 and 2016 for NHPI faculty (p < .001; Brodt et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Yet the number of underrepresented biomedical researchers, particularly those who identify as Black, Latinx, and Native American, remains alarmingly low [1,[8][9][10]. Even when researchers from underrepresented groups pursue biomedical research careers, there continues to be significant attrition [11] and lower rates of promotion than among their non-Latinx White counterparts [12].…”
Section: Introductionmentioning
confidence: 99%